2018
DOI: 10.1182/blood-2017-10-810366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic investigation, clinical features, and response to treatment in 21 patients with Schnitzler syndrome

Abstract: Key Points We found no evidence of somatic NLRP3 mosaicism in the pathogenesis of Schnitzler syndrome. Pathogenic inflammasome activation is supported by increased ASC, IL-18, IL-6, and anakinra response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 29 publications
2
91
1
11
Order By: Relevance
“…No germline pathogenic mutations have been identified so far in patients with Schnitzler syndrome, but somatic mosaicism of NLRP3 involving the myeloid lineage has been reported in two patients with variant Schnitzler syndrome . Yet, these results were not confirmed in a larger cohort of patients with Schnitzler syndrome …”
Section: Pathogenesis and Associated Diseasesmentioning
confidence: 92%
See 2 more Smart Citations
“…No germline pathogenic mutations have been identified so far in patients with Schnitzler syndrome, but somatic mosaicism of NLRP3 involving the myeloid lineage has been reported in two patients with variant Schnitzler syndrome . Yet, these results were not confirmed in a larger cohort of patients with Schnitzler syndrome …”
Section: Pathogenesis and Associated Diseasesmentioning
confidence: 92%
“…Since its original description, NUD has been accepted as an autonomous entity. Numerous new cases have been reported, and associated diseases have been confirmed and expanded . Table summarizes the associated diseases that have been published since our original publication in 2009.…”
Section: Introduction and Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Through sequencing the entirety of the NLRP3 gene, we excluded the notion that NLRP3 mutations are responsible for the pathologic development of SchS, which strengthens our previous findings. Including the 21 patients in our previous study , we have now excluded somatic NLRP3 mutations in 32 SchS patients. Nevertheless, NLRP3 activation still likely plays a part in the etiology of SchS, given previous data establishing elevated levels of ASC aggregates and IL‐18 in SchS patients; similar quantities were found in CAPS patients, which not only reinforced the similar pathology between the 2 diseases, but was also highly indicative of inflammasome activation .…”
Section: Discussionmentioning
confidence: 99%
“…Lately, cases of late‐onset acquired CAPS (aCAPS) have been characterized, caused by somatic mutations in the NLRP3 gene . Results of one study suggested that myeloid‐restricted somatic mutations in NLRP3 may contribute to the pathogenesis of SchS , although a larger study of 21 SchS patients failed to identify any somatic mutations in either NLRP3 or 31 other genes associated with autoinflammatory disorders .…”
Section: Introductionmentioning
confidence: 99%